Analysis of the Influence of Financial Literacy and Consumptive Behavior on Students' Investment Decisions in the Digital Era - Prakoso, Teguh; Apriliani, Rina (Borong Newinera Publisher, 2026)
This study aims to analyze the influence of financial literacy and consumer behavior on students' investment decisions in the digital era. The research method used was quantitative with a survey approach. The research sample consisted of 120 Management Study Program students selected by purposive sampling. The research instrument used a questionnaire with a Likert scale of 1-5. Data analysis was performed using multiple linear regression with the help of SPSS. The results showed that financial literacy had a positive and significant effect on students' investment decisions, while consumer behavior had a negative and significant effect on investment decisions. These findings indicate the importance of improving financial literacy and controlling students' consumer behavior in making investment decisions in the digital era.